Optimizing tourism industry performance strategy selection: an analytical hierarchy process perspective - Achmad, Fandi; Rizaldi, Artamevia Salsabila; Sriwana, Iphov Kumala; Rumanti, Augustina Asih (Universitas Mercu Buana, 2023)
The tourism industry has an important role in a region's economic growth and development. However, the success of the tourism industry is highly dependent on the strategic policies adopted to increase optimal performance. One way to increase the optimal performance of the tourism industry is to maximize support system facilities. Therefore, this study aims to optimize the performance of the tourism industry by selecting the right strategy based on the support system facilities variable. Support system facilities include telecommunication, power sources, transportation, waste management, location, clean water sources, supporting industries, spatial, hospitality, safety, and security. The Analytical Hierarchy Process (AHP) method selects strategies based on support system facilities. Data is collected through a survey of tourism industry experts and related stakeholders. The results of this study indicate that indicators with high-ranking weights are telecommunication, spatial, and waste management, respectively. Each indicator is calculated for each sub-indicator to find out more in detail about producing the relative priority of the strategy. The analysis shows the importance of each factor in influencing the tourism industry's performance to assist decision-makers in planning and implementing effective strategies. Alternative strategies are prepared based on calculating the weighting of the criteria and sub-criteria. By considering support system facilities as an important factor, strategic decisions can be taken based on clear and measurable preferences.